Learning of Qur'an Memory in Realizing Qur'anic Resources in Sampit Kota Batam - Syafrinal Syafrinal; Ilyas Husti; Zamsiswaya Zamsiswaya (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the learning of Quran memorization in realizing Quranic resources at SMPIT Batam City. The purpose of this study was to determine the learning of Quran memorization, identify the challenges faced by teachers, describe the factors that influence learning, and determine the methods used in learning Quran memorization at SMPIT Batam City. The study was conducted in four schools: SMPIT Ulil Albab, SMPIT Fajar Ilahi Batu Aji, SMPIT Fajar Ilahi Sungai Beduk, and SMPIT El-Yasin. The research method used a qualitative approach with data collection techniques through observation and interviews. The results showed that the four schools implemented a tahfidz program with different characteristics. SMPIT Ulil Albab implemented the most structured program with five main methods (Talaqqi, Tikrar, Muraja'ah, Wahdah, and Jama') and the Munaqosyah evaluation system. SMPIT Fajar Ilahi (both branches) focused on the joint muroja'ah method and independent memorization with differentiation programs such as AOT (Acceleration of Tahfidz). SMPIT El-Yasin used a more flexible approach. The success rate of the program varied between 60-70%, with SMPIT El-Yasin recording the highest success rate. Spiritual impacts were consistently seen in all schools, including improvements in the quality of worship, prayer discipline, and improvements in student morals. The main challenges faced included limited learning time, a less than ideal teacher-student ratio, and limited learning media. In conclusion, despite variations in implementation and methodology, all four schools succeeded in achieving the main goal of forming a Qur'anic generation. Key success factors included a systematic approach, realistic targets, intensive guidance through the halaqoh system, and effective collaboration between teachers, students, and parents.